PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL PROVINSI DKI JAKARTA - Ayu Sekar Rini Ardiawati; Amn Zarkasyi Rahman; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Employee performance is the main driver in achieving the success of an organization's goals. Therefore, the performance of the employees of DKI Jakarta Province must always be improved in order to provide good public services to the community. It is known that leadership and motivation have not been fully effective given to all employees which is not adapted to changing conditions. This study aims to determine the effect of leadership, motivation on employee performance, and to determine the effect of leadership and motivation on employee performance. The methodology of this research is a quantitative research method. Data collection techniques in this study used a questionnaire and observation. The data analysis technique used is validity test, reliability test, and regression test. Based on the research results, the following conclusions can be drawn: (1) There is an influence between leadership on employee performance in DKI Jakarta Province, as evidenced by the acquisition of the coefficient value r = 0.356 and , 2.99 > 1.96 with sig. 0.002 (p. 1.96 with sig. 0.000 (p.3.191 with sig. 0.000 (p